Digital Technologies and Virtual reality (VR) as therapeutic intervention for stress reduction in ASD - Sideraki, Angeliki; Stathopoulou, Agathi (Eximia, 2023)
A promising tool has recently appeared in many areas called virtual reality. Virtual reality (VR) is real-world simulation based on computer graphics and can be used as an educational and therapeutic tool by educators and therapists to provide children with a safe learning environment. Below are studies to demonstrate the effectiveness of virtual reality in reducing stress in individuals with autism and promoting the development of emotional skills.